2020
DOI: 10.1039/d0ta04083e
|View full text |Cite
|
Sign up to set email alerts
|

Azine-based polymers with a two-electron redox process as cathode materials for organic batteries

Abstract: Azine-based polymers as cathode-active materials with a two-electron redox process show a high specific capacity of up to 133 mA h g−1 in Li–organic batteries at potentials of 2.9 and 3.3 V vs. Li/Li+ paired with a high rate performance up to 100C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…[ 14 ] For high performance of such cells, the organic electrode materials must show a reversible redox chemistry [ 15 ] and ideally possess a high specific capacity. [ 16,17 ] To obtain high cycling stabilities, dissolution of the organic active material in the liquid battery electrolyte has to be avoided, for which incorporation into a polymeric architecture has been proven a viable strategy. [ 18–20 ] Both p‐type organic redox polymers with potentials of up to 4.1 V versus Li|Li +[ 21 ] as prospective positive electrode materials as well as n‐type redox polymers as negative electrode materials have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] For high performance of such cells, the organic electrode materials must show a reversible redox chemistry [ 15 ] and ideally possess a high specific capacity. [ 16,17 ] To obtain high cycling stabilities, dissolution of the organic active material in the liquid battery electrolyte has to be avoided, for which incorporation into a polymeric architecture has been proven a viable strategy. [ 18–20 ] Both p‐type organic redox polymers with potentials of up to 4.1 V versus Li|Li +[ 21 ] as prospective positive electrode materials as well as n‐type redox polymers as negative electrode materials have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Low redox potential polymers are particularly attractive to obtain full‐organic cells with large operating voltages, and redox‐active groups with two‐electron processes will increase the specific capacities of the corresponding redox polymers. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…The most well‐known p‐type organic cathode materials are conducting polymers (e. g., polyaniline, [11,12] polytriphenylamine, [13] and polypyrrole [14] ) and nitroxyl radical polymers (e. g., PTMA [15] ). In recent years, researchers’ interest also shifts to polymers based on various electroactive heteroaromatics, including N ‐substituted phenazine, [16–19] conjugated pyridine dimer, [20] phenothiazine, [18,21–31] phenoxazine, [32] and thianthrene [33,34] . A merit of these heteroaromatic units is that they are potentially able to deliver two electrons and thus achieve attractive capacity above 200 mAh g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Acker et al. [ 198 ] reported a crosslinked azine‐based polymer (CPA) (Figure 20d). It had two cathodic/anodic peaks at 2.6/2.85 and 3.1/3.31 V (Figure 20e).…”
Section: Organic Polymer Electrode Materialsmentioning
confidence: 99%
“…[197] Unlike triazine polymers, the azine and viologen polymers are p-type polymers and undergo a twoelectron redox process (Figure 20c). Acker et al [198] reported a crosslinked azine-based polymer (CPA) (Figure 20d). It had two cathodic/anodic peaks at 2.6/2.85 and 3.1/3.31 V (Figure 20e).…”
Section: Imine Polymersmentioning
confidence: 99%